Synthesis of C3-Cyanomethylated Imidazo[1,2-a]pyridines via Ultrasound-Promoted Three-Component Reaction under Catalyst- and Oxidant-Free Conditions - Zhang, Jie; Zhang, Yufeng; Zhang, Jian; Wu, Qingguo; Yang, Haifeng (Synlett, 2022)
An efficient synthesis of C3-cyanomethylated imidazo[1,2-a]pyridines via ultrasound-promoted three-component reaction under catalyst-free, oxidant-free, and mild conditions has been developed. A series of C3-cyanomethylated imidazo[1,2-a]pyridines were rapidly prepared with satisfactory yields and good functional group compatibility. This strategy cloud also be applied to the synthesis of zolpidem and alpidem in short steps.
Keywords: ultrasonic irradiation; three-component reaction; cyanomethylation; imidazopyridines; catalyst- and oxidant-free